Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Matematika Bertipe HOTS Berdasarkan Teori Newman - Febryana, Eka; Sudiana, Ria; Pamungkas, Aan Subhan (SJME (Supremum Journal of Mathematics Education), 2023)
This study is a descriptive study that aims to describe the errors made by students in solving high order thinking skills (HOTS) type math problems based on Newman. This research was conducted at SMP Negeri 1 Majasari, Pandeglang Regency with a research subject of 21 students, which will then be selected as many as 6 students to be interviewed. The research instrument used in this research is a test instrument in the form of a HOTS-type math problem with 3 straight-line equations as well as interview guidelines. The results of the study obtained information that the errors made by students when working on high order thinking skills (HOTS) type math problems with Straight Line Equations material were divided into five types of error categories, namely reading errors (errors in reading problems) of 3.6% , comprehension error (error in understanding the problem given) by 28.8%, transformation error (error in problem transformation) by 11.2%, processing skill error (error in process skill) 31.6%, and encoding error (error in processing skill). coding or conclusion error)24.8%.